A&T India Maternal Nutrition COVID-19 Phone Survey 2020: Households – Recently Delivered Women - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
This dataset is the result of the household/mother’s survey that was conducted to gather data during the COVID-19 pandemic as a follow up to the impact evaluation study of the Alive & Thrive (A&T) interventions delivered through the Reproductive, Maternal, Newborn, Child Health (RMNCH) services in India. These include provision of iron and folic acid (IFA) and calcium supplements, interpersonal counseling on diet during pregnancy and consumption of IFA and calcium, community mobilization, and adequate weight-gain monitoring during pregnancy. A&T is a global initiative that supports the scaling up of nutrition interventions to save lives, prevent illnesses, and contribute to healthy growth and development through improved maternal nutrition, breastfeeding and complementary feeding practices. Using a cluster randomized evaluation design, the primary objectives of the A&T evaluation study in India are to answer the following questions : (1) Can the coverage and utilization of key maternal nutrition interventions be improved by integrating nutrition-focused social behavior change (SBC) communication and systems strengthening approaches into antenatal care (ANC) services under the RMNCH program? (2) What factors affect effective integration of maternal nutrition interventions into a well-established government ANC service delivery platform under the RMNCH program? (3) What are the impacts of the program on i) consumption of diversified foods and adequate intake of micronutrient, protein, and energy compared to recommended intake; ii) intake of IFA and calcium supplements during pregnancy; iii) weight gain monitoring; and iv) early initiation of breastfeeding. As with the main impact evaluation, the COVID phone survey used the same 26 blocks in Uttar Pradesh. Thirteen blocks from two districts (Kanpur Dehat and Unnao) were randomly allocated to receive intensified maternal nutrition interventions. Another 13 blocks from the same two districts were randomly allocated to the comparison groups. The survey took place between August and September 2020 by the team from International Food Policy Research Institute (IFPRI), in collaboration with the survey firm, NEERMAN (Network for Engineering and Economics Research and Management). The COVID phone survey comprised 2 questionnaires: 1) Household questionnaire for mothers with children <2 years of age, and 2) Frontline health workers questionnaire. The household survey for mothers captured information on exposure to health and nutrition services during the COVID-19 pandemic, household food security, infant and young child feeding practices, household food consumption, knowledge, and coping strategies.